(untitled) (American Journal of Islam and Society, 2000)
Despite the instability usually attributed to the Middle East, today one finds an unusual level of stability in eight of its monarchies. When mosl countries of the world are converting to some form of "democracy," what has led this type of state system to such stability? In his book, All in the Family, Michael Herb, Assistant Professor of Political Science at Georgia State University, provides the most thought-provoking work on Middle Eastern monarchies since rentier state theory became fashionable. Herb determines that "there are two distinct forms of monarchism in the Middle East. One is resilient and the other is not’’ (p. 235). His basic thesis is that the key to the survival, persistence, and resilience of monarchies in the Middle East is the willingness and ability of the ruling families to saturate the most important positions in the state apparatus. He terms this "dynastic monarchism"-the idea that "the ruling family forms itself into a ruling institution, monopolizing the key offices of the state" (p. 235). In the unsuccessful type of monarchy, the king "maneuvers among various forces-the army, the parliament, and the parties-and when he loses balance the monarchy falls" (p. 235). Case studies are used to illustrate both monarchical models: dynastic (Kuwait, Saudi Arabia, Qatar, United Arab Emirates, Bahrain, and Oman) and nondynastic (Libya, Egypt, Iraq, Iran. Morocco, Jordan, and Afghanistan - usually excluded from studies on the Middle East). This book relies on comparative analysis and is based not only on archival research, but also on interviews and secondary sources. In the second and third chapters, "The Emergence of Dynastic Monarchy and the Causes of Its Persistence" and "Arabian Society and the Emergence of the Petro-State," respectively, the reader gets a sense of the rise of the petro-state and how it enabled dynastic monarchies to emerge. He asserts that they emerged because the ruler’s relatives "had powerful bargaining resources which they could use to help rulers stay in power, to aid aspiring rulers in achieving power, or to attack and depose sitting rulers" (p. 22). Tims, the emergence of the petro-state added another dimension in intrafamily negotiations. Dynasties consolidate power by limiting the status of any individual or clique. Coalitions are built by the rulers through distribution of government positions to relatives as a means of assuring their cooperation. Dynasties are strengthened by forming consensus on the issue of succession rather than depending on primogeniture. As a result, a ruler is held accountable to his family who ...